How to implement the self-preferencing ban in the European Union's Digital Markets Act - Christophe Carugati (Bruegel, 2022)
Large online platforms are intermediaries between end-users and business users. They sometimes propose their own products and services alongside those of rivals. This can lead to platforms promoting their offers over those of competitors in so-called self-preferencing. The European Union Digital Markets Act (DMA) bans large online platforms under its scope from treating their own products and services more favourably that those of rivals when ranking, crawling and indexing. Platforms - or gatekeepers in the DMA definition - should apply transparent, fair and non-discriminatory conditions when ranking products and services. However, the identification, detection, compliance with and monitoring of self-preferencing is complex and resource-intensive. It requires a case-by-case approach and access to and analysis of platform data and algorithms. The DMA allows gatekeepers to promote their own products and services if rivals are subject to the same treatment. Nonetheless, the DMA neither defines equal treatment nor the main elements of self-preferencing, thus preventing platforms within the DMA's scope from correctly applying the prohibition. To ease enforcement, the European Commission should issue guidance on what constitutes self-preferencing under the DMA, outlining two main principles. First, gatekeepers should use objective and unbiased parameters to determine ranking, indexing and crawling. Second, gatekeepers should demonstrate equal treatment. The guidance will make compliance easier. The Commission should then monitor compliance by appointing and ensuring sufficient rotation of external auditors to avoid capture by gatekeepers. The Commission should also work with competent national authorities that develop technological tools. When monitoring flags a risk of non-compliance, the Commission should then further specify the ban on self-preferencing on a case-by-case basis.
Keywords: 330